Accuracy and Precision Evaluation of International Standard Spherical Model by Digital Dental Scanners. (9th December 2020) - Cai, Hong Xin; Jia, Qi; Shi, HaoYu; Jiang, Yujie; Xue, Jingnan; Chen, ChunXu; Gong, Haotian; Liu, Jie; Lee, Eui-Seok; Jiang, Heng Bo
Abstract : With the popularization of digital technology and the exposure of traditional technology's defects, computer-aided design and computer-aided manufacturing (CAD/CAM) has been widely used in the field of dentistry. And the accuracy of the scanning system determines the ultimate accuracy of the prosthesis, which is a very important part of CAD/CAM, so we decided to evaluate the accuracy of the intraoral and extraoral scanners. In this study, we selected the sphere model as the scanning object and obtained the final result through data analysis and 3D fitting. In terms of trueness and precision, the scanner of SHINING was significantly different from that of others; however, there was no significant difference between TRIOS and CEREC. SHINING showed the lowest level of accuracy, with CEREC slightly lower than TRIOS. The sphere model has also been proven to be scanned successfully.